Proceedings of the Ninth ACM Conference on Hypertext and Hypermedia : Links, Objects, Time and Space---Structure in Hypermedia 1998
DOI: 10.1145/276627.276652
|View full text |Cite
|
Sign up to set email alerts
|

Inferring Web communities from link topology

Abstract: The World Wide Web grows through a decentralized, almost anarchic process, and this has resulted in a large hyperlinked corpus without the kind of logical organization that can be built into more tradit,ionally-created hypermedia.To extract, meaningful structure under such circumstances, we develop a notion of hyperlinked communities on the www t,hrough an analysis of the link topology.By invoking a simple, mathematically clean method for defining and exposing the structure of these communities, we are able to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
303
0
4

Year Published

2000
2000
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 526 publications
(308 citation statements)
references
References 16 publications
1
303
0
4
Order By: Relevance
“…The first was HITS, which is described in [11], and offers some enlightening practical remarks. The ARC system, described in [7], augments Kleinberg's link-structure analysis by considering also the anchor text, the text which surrounds the hyperlink in the pointing page.…”
Section: Introductionmentioning
confidence: 99%
“…The first was HITS, which is described in [11], and offers some enlightening practical remarks. The ARC system, described in [7], augments Kleinberg's link-structure analysis by considering also the anchor text, the text which surrounds the hyperlink in the pointing page.…”
Section: Introductionmentioning
confidence: 99%
“…These vectors are the principal eigenvectors of the matrices AA T and A T A. Work in [54,77] has shown that the concepts of hubs and authorities is a fundamental structural feature of the web. The CLEVER system [29] builds on the algorithmic framework of hub and authorities.…”
Section: Mining the Webmentioning
confidence: 99%
“…An interesting problem associated with the Web is the definition and delineation of so called Web communities [9], [10], [11], [12], [13], [14]. A web community is loosely defined to be a collection of content creators that share a common interest or topic and manifests itself as a highly interconnected aggregate or subgraph [9].…”
Section: Web Communitiesmentioning
confidence: 99%
“…In order to coalesce concepts A, C, D and the concept labelled I, we need to introduce edges (4, 2) and (5, 9) to relation I in order to make the bipartite graph defined by {1, 3, 4, 5, 7}, {2, 6, 9} complete. To coalesce concepts B, E, F, and H, we need to add (2, 12), (6,11) and (8,11) to the original relation to make the bipartite graph defined by {2, 6, 8, 9}, {10, 11, 12} complete. …”
Section: A Simple Examplementioning
confidence: 99%